CROP RAIDING BY HIMALAYAN BLACK BEAR: A MAJOR CAUSE OF HUMAN-BEAR CONFLICT IN MACHIARA NATIONAL PARK, PAKISTAN - S. Shabi-Ul-Hassan Kazmi; R. A. Minhas; B. Ahmad; M. S. Awan; S. Abbasi; U. Ali; U. Shakeel; N. I. Dar (Journal of Animal and Plant Sciences, 2019)
Human–black bear (Ursus thibetanus) conflict is one of the major conservation and rural livelihood issue in Azad Jammu and Kashmir (AJK). Mitigation strategies of such conflicts require a firm understanding of their underlying patterns. To understand these human-black bear conflict patterns with special reference to crop raiding, present study was conducted from April to December 2011 in Machiara National Park (MNP), Azad Jammu and Kashmir, Pakistan. Field (n=30) and questionnaires (n=108) surveys were conducted in three union councils of MNP to collect information on patterns of crop raiding by black bear, local tolerance and perception about black bear during 2007-2011. About 945 acres area with 53.88 metric tons estimated maize crop yield was damaged by black bears during five years. The maximum (33.94%) of crop raiding was reported between elevation range of 2164 and 2285 m above sea level (asl.) along the boundary of the national park (61%) during 1801-0200 hours (69%). Maximum crop raiding was recorded during year 2011 (18.2 metric tons), while the maximum incidences of crop raiding were reported in the month of October (68.51%). The financial value of the damaged crop, according to the local market, was estimated as 1.370 million PKR (US$=14732.258) as per the currency values during the study period. In response, 11 black bears were killed by the community during 1998-2011, while five incidents of bear attacks on human were also recorded. Accordingly, 82% of respondents disliked black bear and suggested its ex-situ conservation (95%). These conflicts are among the main issues, which not only affect the livelihood of poor local villagers but also create serious threats to the conservation of these threatened bears in the area. To improve the local livelihood prospects and black bear protection around the study area, a proper research-based conflict mitigation strategy is seriously required.
Keywords: Crop raiding; black bear (U rsus thibetanus); human-bear conflict; Machiara National Park